The Mediating Role of Green Innovation in the Effect of ESG Practices on Firm Value : Evidence from Southeast Asia - Veronika Geani; Erna Widiastuty (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2026)
Environmental, Social, and Governance (ESG) practices are increasingly adopted by companies. However, the mechanism through which ESG practices enhance firm value still requires further empirical evidence, particularly regarding the mediating role of green innovation in companies operating in the ASEAN region. This study aims to examine the mediating role of green innovation in the relationship between ESG practices and firm value. The sample consists of 300 firm-year observations of companies listed on ASEAN stock exchanges during the 2019–2023 period, selected using a purposive sampling method. Panel data are analyzed using R-Studio through panel regression and mediation analysis. The results indicate that ESG practices have a positive and significant effect on firm value, both directly and indirectly through green innovation. These findings enrich the literature on the mechanism through which ESG creates firm value and provide practical implications by highlighting that the integration of ESG practices and green innovation constitutes an important strategy for enhancing sustainable firm value. Praktik Environmental, Social, and Governance (ESG) semakin luas diadopsi oleh perusahaan. Mekanisme yang menjelaskan bagaimana praktik ESG meningkatkan nilai perusahaan masih memerlukan bukti empiris, khususnya melalui peran green innovation pada perusahaan di kawasan ASEAN. Penelitian ini bertujuan menguji peran mediasi green innovation pada pengaruh praktik ESG terhadap nilai perusahaan. Sampel penelitian terdiri atas 300 observasi perusahaan-tahun perusahaan yang terdaftar di pasar saham ASEAN selama periode 2019–2023 yang dipilih menggunakan metode purposive sampling. Data panel dianalisis menggunakan perangkat lunak R-Studio dengan pendekatan regresi data panel dan analisis mediasi. Hasil penelitian menunjukkan bahwa praktik ESG berpengaruh positif dan signifikan terhadap nilai perusahaan, baik secara langsung maupun tidak langsung melalui green innovation. Temuan ini memperkaya literatur mengenai mekanisme penciptaan nilai melalui ESG serta memberikan implikasi praktis bahwa integrasi praktik ESG dan green innovation merupakan strategi penting untuk meningkatkan nilai perusahaan secara berkelanjutan.